Histological and immunohistochemical characterization of 17 gonadal tumours in koi carp (Cyprinus carpio koi). Issue 3 (24th October 2020) - Sirri, Rubina; Tura, Giorgia; Budai, Jane; Beraldo, Paola; Fiorentino, Michelangelo; Barbé, Tim; Galeotti, Marco; Sarli, Giuseppe; Mandrioli, Luciana
Abstract: Reports on abdominal tumours in koi carp are scarce and most are from the gonads. Their histological diagnosis is challenging due to the occurrence of mixed populations of neoplastic cells and the few availability of cross‐reactive antibodies in fish tissues. The present study aims to provide a histopathological characterization of seventeen gonadal tumours, enriched by a wide antibody panel (vimentin, CD117, placental alkaline phosphatase—PLAP, AE1/AE3 cytokeratin, E‐cadherin, proliferating cell nuclear antigen—PCNA, müllerian‐inhibiting substance—MIS, GATA4 and Inhibin‐α) applied on whole and tissue microarray (TMA) sections. Abdominal enlargement was associated with tumours filling 30%–80% of the abdominal cavity; frequently, the gonads had been completely replaced by neoplastic tissue. Twelve cases were characterized as sex cord‐stromal tumours (SCSTs), three as germ cell tumours (GCTs), one as mixed germ cell sex cord‐stromal tumour (MGCSCST) and one as carcinoma. By immunohistochemistry, PLAP enabled confirmation of GCTs, ovarian carcinoma and the objective identification of a further cell component in 8 out of the 12 SCSTs that were reclassified as mixed tumours. The use of an immunohistochemical panel can help in refining the histological diagnosis, but the morphological diagnosis still represents the main tool for the characterization of these tumours in koi carp.